Nova estratégia para descoberta de anti-helmínticos utilizando o organismo modelo Caenorhabditis elegans - Cintra, Giovana Aparecida De Souza [UNIFESP] (2019)
Diseases caused by soil-transmitted helminths are among the most common infections in the world, affecting marginalized, low-income and resource-poor populations. It is estimated that more than one billion people, especially in developing countries in Africa, Asia and America, are infected with one or more species of helminths. The emergence of resistance to the main anthelmintics used highlights the need for the introduction of new therapeutic agents. The free-living nematode Caenorhabditis elegans is widely recognized as a model organism for investigating the biology of parasitic nematodes due to its easy laboratory culture, short generation time and fully sequenced genome. Most commercial anthelmintics are active against C. elegans, levamisole and benzimidazole derivatives, and this animal model has been useful in understanding the mechanism of action of the same, making it a useful system for selection and investigation of compounds with potential anthelmintic activity. The methodologies currently used to identify new compounds are based on the subjective evaluation of the motile worms, or involve transgenic organisms. In this way there is a need for the establishment of a more objective, sensitive and reproducible biological assay. In the present study the development and standardization of a new methodology of in vivo high content screening using the C. elegans is described. The assay is based on viability assessment by differential incorporation of two fluorescent molecular markers, DB-1, derived from the 2,1,3- benzothiadiazole core and propidium iodide. This model stands out from the previous tests for using an automated imaging platform and later analysis of the images by commercial software, thus quantitatively evaluating the viability in an objective way. In addition, it allows the use of animals without genetic modifications. The establishment of a robust and reproducible assay allowed the screening of 2280 compounds, which are part of three libraries: (i) the commercial LOPAC library, from which three compounds with a potency up to 400x greater than levamisole hydrochloride were selected; (ii) the library of compounds / extracts from different collaborators, with new therapeutic and chemical classes; (iii) the Pathogen Box library, from which three previously reported compounds with activity against malaria, schistosomiasis and tuberculosis were identified. The candidates identified in this work are starting point for studies of medicinal chemistry, aiming to improve their potency and effectiveness. It is also worth noting that two of the compounds selected in the collaborator screening reduced the parasitemia in the in vivo model of Ascarissum infection by 61.96% and 59.78%, confirming the translational value of the C. elegans biological model. In conclusion, the assay developed in this work was successfully established and provides a solid contribution to the initial phases of the discovery of new anthelminthic drugs.